Learning Mathematics Formulas by Listening and Reading Worked Examples - Maryati, Wahyuni Eka; Retnowati, Endah; Thoe, Ng Khar (Indonesian Journal of Teaching in Science, 2022)
This study aims to examine whether there is a significant difference between the effectiveness of worked examples with voice notes and worked examples without voice notes and their relations with computational thinking skills. Both learning strategies were implemented in the derivative of polynomial algebraic function learning. This quasi-experimental study involved 62 students and employed a pre-test and post-test non-equivalent control group design via WhatsApp group. Data were analyzed using ANCOVA with student initial ability measured during the pretest as the covariate. The study empirically proved that there is a significant difference in terms of the effectiveness of both learning strategies viewed from student cognitive load. Worked example without voice notes was more effective and makes students have less cognitive load during learning. In addition, there was no significant difference in the effectiveness of learning strategies in terms of computational thinking skills. This study showed that adding voice notes may lead to redundancy effects, hence the use voice notes with worked examples should be thoroughly considerated.